Even happier [ a gratitude journal for daily joy and lasting fulfillment - Ben-Shahar, Tal (McGraw-Hil, 2010)
The bestselling author of Happier presents a week-by-week journal of gratitude that allows readers to reflect on what they are grateful for in their lives--one of the key ingredients for happiness--as well as 50 new meditations on happiness and fulfillm